Pemanfaatan Kecerdasan Artifisial untuk Digitalisasi Manajemen Acara dan Pelayanan di Gereja Kristen Jawa Condongcatur, Yogyakarta - Qintara Wiksa Satyawira; Axel Nathaniel Kurniawan; Farhan Januarizal; Grant Marks Siregar; Yulius Harjoseputro (Jurnal Atma Inovasia, 2026)
In the era of digital transformation, artificial intelligence (AI) is increasingly used to support organizational management and service delivery across sectors, including religious institutions. Gereja Kristen Jawa (GKJ) Condongcatur, a local church community in Yogyakarta, has basic digital infrastructure but continues to face challenges such as limited AI literacy, fragmented technology use, and insufficient innovation in event management and administrative processes. To address these issues, we implemented an eight-week community service program involving structured training and mentoring on AI tools for digital event management and church ministry. The program involved 12 participants, consisting of church board members and representative congregants, and included three main sessions: an introduction to AI and its potential applications in church ministry; hands-on Workshops on digital content creation using ChatGPT and Canva AI; and AI-based event management and follow-up planning. Evaluation was conducted through a questionnaire distributed to all participants. The results showed that 98% of respondents provided positive feedback across all program stages. These findings demonstrate that the program delivered significant benefits in terms of material relevance and implementation effectiveness. Overall, AI-based training and mentoring can enhance digital literacy and support sustainable digital transformation in church ministry.